Community Perspective in Village Fund Management in Nagur Village, Serdang Bedagai Regency - Aditia Darma Nasution, Dito; Welly, Yerisma (Future Science, 2023)
The research aims to determine the community's perspective in managing village funds in Nagur Village, Serdang Bedagai Regency. The research model was carried out using a descriptive approach with data collection techniques carried out by distributing questionnaires, observations and interviews. The research population was 100 people with a selected sample of 80 samples carried out using a purposive sampling approach. The results of the research explain that the management of village funds from a community perspective in Nagur Village produces a level of satisfaction in the